O erotismo elegíaco nos "amores" de ovídio - Bazerra, Bruno Alacy Nunes (2016)
This research has as goal to study the eroticism present in Ovid’s Amores, one of the great names of Latin Elegy of century I B.C. The main focus is to analyze the several erotic passages throughout the work, especially in our corpus, constituted by three elegies (Am. I.5, Am. II.15 and Am. III.7), which will be thoroughly analyzed in a specific chapter. Our study is supported by theorists that discuss literary and cultural aspects - History, Religion and Sociology - of the Roman thought of the time, in order to elaborate a work without anachronisms. We present operating translates os the originals texts analyzes during the research, including our complete translations of the three elegies that compose the corpus, aiming a better understanding of the text and its posterior analysis.